2014
DOI: 10.1007/s13595-013-0349-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of wood quality attributes in Western Larch

Abstract: & Context Wood quality traits are important to balance the negative decline of wood quality associated with selection for growth attributes in gymnosperm breeding programs. Obtaining wood quality estimates quickly is crucial for successful incorporation in breeding programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
(41 reference statements)
2
7
0
5
Order By: Relevance
“…As expected for black spruce, there were weak G × E interactions for wood traits in both subzones. These results agree with those of many other studies on conifers (Johnson and Gartner 2006, Chen et al 2014, Ratcliffe et al 2014.…”
Section: Discussionsupporting
confidence: 93%
“…As expected for black spruce, there were weak G × E interactions for wood traits in both subzones. These results agree with those of many other studies on conifers (Johnson and Gartner 2006, Chen et al 2014, Ratcliffe et al 2014.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, these stands were analysed for SWV and SWV and was found to be significantly positively correlated to height and DBH. A similar correlation was also found by El-Kassaby et al [45], Lenz et al [12], Li et al [46], Ratcliff et al [47] and Wielinga et al [48].…”
Section: Discussionsupporting
confidence: 84%
“…Estimates of the heritability of SWV are widely available. For example, Lenz et al [12] observed a heritability of 0.78 in white spruce and Ratcliff et al [47] observed (Rep = 0.42) in western larch (Larix occidentalis Nutt. ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Zobel and van Buijtenen (1989) also have emphasized that wood quality improvement should be an integral part of tree breeding programs. However, because a negative decline of wood quality associated with the selection for growth characteristics has been concerned in tree breeding programs, selecting plus-trees based on wood quality is important (Ratcliffe et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Young's modulus has been also known to have major effect on product design and important in engineering (Bucur 2006). In addition, a rapid estimation of wood quality is crucial for the success of wood quality improvement in tree breeding programs (Ratcliffe et al 2014). Therefore, SWV is important and appropriate for evaluating Young's modulus of wood in tree breeding programs.…”
Section: Introductionmentioning
confidence: 99%